2021
DOI: 10.3390/horticulturae7110462
|View full text |Cite
|
Sign up to set email alerts
|

Quality Responses of Table Grapes ‘Flame Seedless’ as Effected by Foliarly Applied Micronutrients

Abstract: Micronutrient (iron, zinc and boron) deficiencies are a basic and prominent factor affecting grape quality and yield in the Pothwar region. To overcome these deficiencies, different levels of micronutrients were applied foliarly on grapevines at five different berry developmental stages during two consecutive growing seasons (2018 and 2019). The data suggested that foliar treatment of micronutrients significantly increased the yield, number of bunches per vine, bunch weight, yield per vines, bunch length, berr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
5
7
0
Order By: Relevance
“…However, non-reducing values were in the range of 1.12% to 2.24%, with a mean value of 1.69 ± 0.37% ( Table 1 ); the maximum and the minimum non-reducing sugars were noticed in vineyard V9 and V1, respectively ( Figure 3 ). Similar to total sugars, the reducing sugars and non-reducing sugars’ variability was reported for Flame Seedless grapes by another author [ 2 ], but a comparison of the presented data with the literature data was not possible. The nine investigated vineyards showed an identical trend for the total sugars, reducing sugars, and non-reducing sugars; however, the highest values of them belonged to vineyard V9 and the lowest values belonged to vineyard V1.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…However, non-reducing values were in the range of 1.12% to 2.24%, with a mean value of 1.69 ± 0.37% ( Table 1 ); the maximum and the minimum non-reducing sugars were noticed in vineyard V9 and V1, respectively ( Figure 3 ). Similar to total sugars, the reducing sugars and non-reducing sugars’ variability was reported for Flame Seedless grapes by another author [ 2 ], but a comparison of the presented data with the literature data was not possible. The nine investigated vineyards showed an identical trend for the total sugars, reducing sugars, and non-reducing sugars; however, the highest values of them belonged to vineyard V9 and the lowest values belonged to vineyard V1.…”
Section: Resultsmentioning
confidence: 65%
“…Jumbo Seedless increased, the concentration of reducing sugars decreased. Additionally, reducing, non-reducing, and total sugars concentrations of grape berries increased with increasing concentrations of micronutrients by applying agronomical management, such as fertilization, additionally, the increase in the sugar content of grape berries could be associated with the increased chlorophyll content [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present study, nine vineyards were selected that differed from one vineyard to another in applied agricultural practices, in particular, fertilization applications, which included fertilization units, fertilizer types, and fertilization dates [61,62]. However, different vines were selected so that they were as uniform as possible in growth with no visual nutrient deficiency symptoms and almost uniform in their vigor to get samples as follows (i.e., 9 vineyards × 9 replicates = 81 vines).…”
Section: Experimental Site and Plant Materialsmentioning
confidence: 99%
“…In the study of Stino et al [58], chlorophyll contents of Flame seedless grapevines in 2014 and 2015 seasons ranged from 2.61 to 3.06 mg/g and 2.65 to 3.22 mg/g, respectively, under the influence of bio-stimulants and the lowest chlorophyll contents belonged to vines treated by water. Furthermore, in leaves of Flame Seedless' as effected by foliarly applied micronutrients, Ali et al [62] reported for control, i.e., vines were treated by water that Chlorophyll A values were 2.47 ± 0.23 and 2.45 ± 0.14 (mg/g) and Chlorophyll B were 1.32 ± 0.18 and 1.03 ± 0.06 (mg/g) for seasons 2018 and 2019, respectively. Furthermore, it is clear from Table 1 that the maximum value of total carotenoids was 5.89 mg/g fresh weight, the minimum value was 3.25 mg/g fresh weight and the average value was 4.58 mg/g fresh weight.…”
Section: Nutritional Status In the Leavesmentioning
confidence: 99%